Effect Consetration of Mollucicides and Variance of Water Height on Paddy Growth and Population of Golden Snail(Pomacea canaliculata L.)at Paddy Field in Tanjung Mulia Village Tanjung Morawa District - Verda Klara Sari Tarigan; Erwin Masrul Harahap; Kemala Sari Lubis (Universitas Sumatera Utara, 2018)
Golden snail (Pomacea canaliculata L.) able breed quickly at flood area and hold out at 6-8 weeks at dry condition. Modification of water heights and concetrations of mollucicides are be expected decrease the population of golden snail (Pomacea canaliculata L.). This research was studied at paddy field of Tanjung Mulia Village, Tanjung Morawa District from April 2016 until August 2016. This research used completely randomized design with two factors consist of water heights of paddy field (H) such as, 0 cm; 2,5 cm; 5 cm and consetrations of mollucicides (M) such as, 0 g/15L water;100 g/ 15L water; 300 g/ 15 L water. Combinations treatment are repeated at three times and there are 27 treatments. The results showed the decreasing of water heights at paddy field can decre the population of golden snail (Pomacea canaliculata L.) and dry grain weight brutto; application of mollucicides showed response about golden snail (Pomacea canaliculata L.) and many parameters of rice; combination of decrease water height in paddy field and consetration of mollucicides did not show response about golden snail (Pomacea canaliculata L.) and many parameters of rice. Key words : golden snail, height water, mollucicides